(untitled) - Pinder, A. R. (London, 1960)
This book introduce the essential oils, determination of structure, acyclic monoterpenes, diterpenes,...
Keywords: Terpenes,Essential oils,Terpene (nhóm các hydrocacbon không no),Tinh dầu